Homogenous and interoperable signaling computer interlocking through IEC 61499 standard - Abourahim, Ikram; Eleuldj, Mohsine; Amghar, Mustapha (International Journal of Electrical and Computer Engineering (IJECE), 2023)
The technological evolution of signaling systems has created a dependency from infrastructure managers to suppliers and industrials dominating the market. Indeed, for each deployed computer interlocking, the modification of field equipment is required to allow an adaptation with the new interlocking in terms of communication protocols and logical interface. In addition, to ensure safe traffic of trains, the communication of railway signaling data is necessary between interlockings. However, delayed deployments from one station to another make the establishment of communication channels costly and difficult, or even impossible, since each supplier keeps confidential its communication protocols and usually opts for interfacing based on wired logic. This paper presents our approach to a homogeneous architecture of interlocking meeting modularity requirements, interoperability, and logical interfacing between interlockings. This approach relies on a classification of internal functions of the computer interlocking, a distribution of the execution of those functions and making useful information available for interfaces between adjacent interlockings through the IEC 61499 standard coupled with service-oriented architecture (SOA).